Evaluation of wind characteristics in Bac Lieu in 2016 using the weibull function - Thanh, Pham Xuan; Anh, Nguyen Xuan; Luu, Le Van; Nguyen, Hiep Van; Son, Hoang Hai; Khuong, Pham Le; Thuy, Do Ngoc (Vietnam Journal of Marine Science and Technology, 2017)
In this paper, the characteristics of wind speed at 20 m height at the Bac Lieu atmospheric physic station (Bac Lieu station) in 2016 were evaluated using the Weibull distribution function. The wind speed data set (every minute) from January 7th  to December 31st, 2016 was used to calculate the two parameters of  Weibull function including Weibull shape factor “k” and Weibull scale factor “c”. The results showed that at the Bac Lieu station in 2016, the values of k and c were 1.69 and 3.91, respectively. Some characteristics of wind speed were also estimated such as wind energy density (Pa/A=57.3 W/m2), wind speed of maximum energy carrier (Vmec=6.2 m/s), the most probable wind speed (Vmp=2.3 m/s), mean wind speed (Vmean=3.5 m/s)  and standard deviation of wind speeds (s = 2.1 m/s).